Lead-based alloy electrochemical corrosion resistance testing device and testing method thereof

By designing a lead-based alloy electrochemical corrosion-resistant test device, using constant voltage current limiting and stirring electrolyte, the problems of plate grid manufacturing process parameters and structural influence and uneven water electrolysis were solved, and the stability of the test results was achieved and Fastness, suitable for the evaluation of corrosion resistance of lead-based alloys.

CN111307706BActive Publication Date: 2024-12-20JIANGSU HAIBAO NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010212821.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-24
Publication Date
2024-12-20
Estimated Expiration
2040-03-24

AI Technical Summary

Technical Problem

The existing electrochemical corrosion resistance test methods of lead-based alloys have problems such as difficult to eliminate the influence of plate grid manufacturing process parameters and structural, uneven water electrolysis and rough calculation of current density, resulting in unstable test results and affecting the design and development progress.

Method used

A lead-based alloy electrochemical corrosion resistance test device is designed, including a tank body, agitator motor, liquid level monitor and reference electrode. Through a constant voltage current-limiting charging test device, a closed circuit is formed using auxiliary electrodes and reference electrodes. , the electrolyte was stirred and the electrolyte was kept stable by level monitoring. After 72 hours of testing, the weight loss percentage was calculated to evaluate corrosion resistance.

Benefits of technology

It achieves good reproducibility, short cycle, simple and fast test results, can accurately evaluate the corrosion resistance of lead-based alloys, and is suitable for rapid design and development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111307706B_ABST
    Figure CN111307706B_ABST
Patent Text Reader

Abstract

The present invention discloses a lead-based alloy electrochemical corrosion resistance test device, comprising a slot body, a handle, an anode slot for placing a comparison electrode and an electrode to be tested, a cathode slot for placing an auxiliary electrode, an anode terminal, a cathode terminal, a stirring motor, a liquid level monitor, a reference electrode mounting hole, a reference electrode terminal, a stirring paddle, a slot baffle, a flow hole, and a water replenishment hole; by matching the comparison electrode, the auxiliary electrode, and the reference electrode, the lead-based alloy is tested for electrochemical corrosion resistance using the test device. The test device and the test method of the present invention have good test result reproducibility, a short test cycle, and are simple and quick, and can be used to quickly evaluate lead-based alloys and lead-based alloy processing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical corrosion resistance testing, and in particular relates to a lead-based alloy electrochemical corrosion resistance testing device and a testing method thereof. Background Art

[0002] The grid of lead-acid batteries is generally made of lead-based alloy. Because the main component of the positive active material of the lead-acid battery is lead dioxide, and the main component of the grid is lead, the two can undergo redox reaction to produce lead oxide; at the same time, because the battery is generally charged by constant voltage and current limiting, the positive electrode potential will rise to above 2.6V, and electrochemical corrosion will occur in the sulfuric acid electrolyte atmosphere, so the corrosion of the grid is inevitable. The corrosion of the grid can be improved and slowed down by designing the lead-based alloy of the grid and the structure of the grid, so that the grid will not affect the battery life due to grid corrosion problems during the entire battery life cycle. Therefore, it is necessary to test the electrochemical corrosion resistance of the lead-based alloy used to prepare the grid.

[0003] The normal life of a battery is more than 3 years, and it takes 150-300 days to conduct a rapid cycle test in the laboratory. Therefore, the normal test cycle is too long, which affects the design and development progress. The commonly used test method for the electrochemical corrosion resistance of lead-based alloys is to combine the positive grid and the negative grid into a battery unit, pass a constant direct current to electrochemically corrode the grid for a period of time, and evaluate the corrosion resistance of the grid or lead-based alloy by calculating the weight loss through testing. There are several problems with testing according to this method: First, the manufacturing process parameters and structure of the grid have a certain influence on the corrosion resistance of the grid. Directly using the grid to test the corrosion resistance of the lead-based alloy cannot eliminate the influence caused by manufacturing and other factors, and cannot accurately evaluate the corrosion resistance of the lead-based alloy; Second, the grid corrosion resistance test process has a voltage higher than the decomposition voltage of water, so a large amount of water will be electrolyzed, the concentration of the electrolyte will be uneven, and the electrolyte concentration will gradually increase, which is a factor affecting the instability of the test results; Third, this method uses a constant current charging method to test the corrosion resistance of the grid. The current density is calculated based on the area of ​​the plate surface. The calculation is relatively rough and cannot reflect the actual current density of the grid interface, which is also a factor affecting the instability of the test results.

[0004] Therefore, it is necessary to design and develop a new technical solution to solve the above problems. Summary of the invention

[0005] The present invention adopts the following technical scheme: a lead-based alloy electrochemical corrosion resistance test device, including a trough body, a handle, an anode slot for placing a comparison electrode and an electrode to be tested, a cathode slot for placing an auxiliary electrode, an anode terminal, a cathode terminal, a stirring motor, a liquid level monitor, a reference electrode mounting hole, a reference electrode terminal, a stirring paddle, a slot baffle, a flow hole, and a water replenishment hole. The handle is installed on the outer side walls on the front and rear sides of the trough body, the anode slot and the cathode slot are relatively parallelly distributed at the front and rear ends of the trough body, the anode slot and the cathode slot are each composed of a pair of slot baffles, and the spacing between each pair of the slot baffles is the same. The slot baffle is vertically inserted into the slot body, and a number of flow holes are evenly distributed on the slot baffle. The anode terminal is fixedly installed at the edge of the top of the slot body on the same side of the anode slot, and the cathode terminal is fixedly installed at the edge of the top of the slot body on the same side of the cathode slot. The stirring motor is installed in the center above the top of the slot body. A stirring paddle is connected below the stirring motor, and the stirring paddle is arranged inside the slot body. A water replenishment hole is arranged on the left side of the stirring motor, and a reference electrode installation hole is arranged on the right side of the stirring motor. The reference electrode installation hole is arranged between the stirring motor and the reference electrode terminal. A liquid level monitor is installed at a corner of the top of the slot body.

[0006] Furthermore, the tank body is the main body of the testing device, and is preferably made of a transparent PC material with a thickness of 5 mm.

[0007] Furthermore, the spacing between each pair of the card slot baffles is preferably 3 mm.

[0008] Furthermore, the diameter of the flow hole is 8 mm.

[0009] A test method for a lead-based alloy electrochemical corrosion resistance test device, the specific test steps are as follows:

[0010] 1) Prepare the electrode to be tested, the reference electrode and the auxiliary electrode; soak the reference electrode in a sulfuric acid aqueous solution for at least 24 hours; prepare the test device; prepare a charging test device with a constant voltage and current limiting function as an auxiliary test device, the charging test device includes a positive electrode output line, a positive electrode voltage collection line, a negative electrode output line and a negative electrode voltage collection line; use a sulfuric acid aqueous solution as the electrolyte, add the electrolyte to the tank body to a liquid level of 120mm; weigh the weight of the electrode to be tested and the reference electrode as m1 and m2 respectively;

[0011] 2) Insert the electrode to be tested and the comparison electrode symmetrically into the anode slot, insert the reference electrode into the reference electrode mounting hole, and insert the auxiliary electrode into the cathode slot; connect the auxiliary electrode to the cathode terminal, connect the electrode to be tested and the comparison electrode to the anode terminal respectively, add electrolyte to the tank body through the water replenishment hole to a liquid level of 125mm, connect the positive output line and the positive voltage collection line of the charging test equipment to the anode terminal, connect the negative output line of the charging test equipment to the cathode terminal, connect the negative voltage collection line of the charging test equipment to the reference electrode terminal, and connect the water delivery hose to the water replenishment hole;

[0012] 3) Start the stirring motor and set the stirring speed to 5 rpm to stir the electrolyte; set the constant voltage of the charging test equipment to 2.6V and conduct a continuous 72h test under this constant voltage; continue stirring during the test and monitor the electrolyte level in the tank through the liquid level monitor. After the liquid level drops, slowly inject pure water or distilled water from the water filling hole to ensure that the electrolyte level is 125±1mm during the entire test;

[0013] 4) After the test is completed, take out the electrode to be tested and the reference electrode from the anode slot, soak them in 60°C sugar-alkali water for 15 minutes to remove the oxides produced by surface electrochemical corrosion, then rinse them with tap water until the surface is bright, and then vacuum dry them at 110°C for 30 minutes;

[0014] 5) Use scissors to cut off the tabs of the electrode to be tested and the reference electrode respectively, weigh the tabs to be m3 and m4 respectively, and weigh the remaining electrodes to be m5 and m6 respectively;

[0015] Calculate weight loss:

[0016] W1=(m5-m3) / (m1-m3)*100;

[0017] W2=(m6-m4) / (m2-m4)*100;

[0018] △W=(W2-W1) / W2*100;

[0019] W1 is the weight loss percentage of the electrode to be tested;

[0020] W2 is the weight loss percentage of the comparative electrode;

[0021] △W is the relative corrosion resistance of the electrode to be tested. When its value is positive, it means that the corrosion resistance of the electrode to be tested is higher than that of the comparison electrode. The higher the ratio, the stronger the corrosion resistance. When its value is negative, it means that the corrosion resistance of the electrode to be tested is lower than that of the comparison electrode. The lower the ratio, the worse the corrosion resistance.

[0022] Furthermore, in step 3), the test method is carried out in a fume hood, and the test device needs to be placed in a constant temperature water bath at 25±2°C.

[0023] Furthermore, in step 1),

[0024] Preparation method of the electrode to be tested: melt the lead-based alloy to be tested, cast it into a 10mm thick lead block, and prepare the lead block into a lead plate with a thickness of 2.5mm and a surface roughness Ra <3μm through multi-stage rolling, and then cut the lead plate into a 60*120mm electrode piece, and leave a 6mm wide and 20mm long pole ear on the upper part of the electrode piece;

[0025] Preparation method of comparison electrode: select a lead alloy that has been tested to meet the alloy standards for battery use and has been used in practice to meet the corrosion resistance design requirements within the normal service life of the battery, and use the same preparation method as the electrode to be tested;

[0026] Preparation method of auxiliary electrode: electrolytic lead with a lead content of 99.994% is selected, and the auxiliary electrode is prepared by the same preparation method as the electrode to be tested.

[0027] Furthermore, in step 1), the aqueous sulfuric acid solution is prepared from analytical pure sulfuric acid and distilled water, and the aqueous sulfuric acid solution is 1.35±0.01 g / ml; the reference electrode is preferably a cadmium electrode.

[0028] Furthermore, in step 2), pure water or distilled water with a conductivity of less than 1 μS / cm is introduced into the water delivery hose; and the connecting components used by the reference electrode, auxiliary electrode, electrode to be tested and comparison electrode are all their own electrode ears.

[0029] Furthermore, the mass ratio of glucose, caustic soda and water in the sugar-alkali water is 1:5:50.

[0030] The beneficial effects of the present invention are: the auxiliary electrode in the present invention enables the circuit in the test method to form a complete closed circuit; the reference electrode in the present invention is a standard electrode with a stable potential, which is used to measure the positive electrode potential; the test device and test method of the present invention have good reproducibility of test results, a short test cycle, and are simple and fast, and can be used to quickly evaluate lead-based alloys and lead-based alloy processing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the structure of the testing device of the present invention.

[0032] Figure 2 It is a three-dimensional diagram of the testing device of the present invention.

[0033] Figure 3 It is an overall schematic diagram of the stirring paddle of the present invention.

[0034] Figure 4 It is an overall schematic diagram of the card slot baffle of the present invention.

[0035] Figure 5 It is an overall schematic diagram of the testing method of the present invention.

[0036] Figure 6 It is a schematic diagram of the structure of the electrode to be tested of the present invention.

[0037] Wherein: 1. trough body, 2. handle, 3. anode slot, 4. cathode slot, 5. anode terminal, 6. cathode terminal, 7. stirring motor, 8. liquid level monitor, 9. reference electrode, 10. reference electrode terminal, 11. stirring paddle, 12. slot baffle, 13. flow hole, 14. auxiliary electrode, 15. comparison electrode, 16. test electrode, 17. water supply hole, 18. reference electrode mounting hole, 19. solenoid valve, 20. solenoid valve data line, 21. control center, 22. liquid level detector data line, 23. charging test equipment, 24. charging test equipment data line, 25. positive output line, 26. negative output line, 27. positive voltage collection line, 28. negative voltage collection line, 29. pole ear, 30. water storage bucket, 31. water delivery hose, 32. test device. DETAILED DESCRIPTION

[0038] like Figure 1-6As shown, a lead-based alloy electrochemical corrosion resistance test device includes a tank body 1 as the main body of the test device, a handle 2, an anode slot 3 for placing a comparison electrode 15 and a test electrode 16, a cathode slot 4 for placing an auxiliary electrode 14, an anode terminal 5, a cathode terminal 6, a stirring motor 7, a liquid level monitor 8, a reference electrode mounting hole 18, a reference electrode terminal 10, a stirring paddle 11, a slot baffle 12, a flow hole 13, and a water replenishment hole 17. The tank body 1 is made of a 5mm thick transparent PC material, the handle 2 is installed on the outer side walls on the front and rear sides of the tank body 1, the anode slot 3 and the cathode slot 4 are relatively parallelly distributed at the front and rear ends inside the tank body 1, the anode slot 3 and the cathode slot 4 are each composed of a pair of slot baffles 12, and the spacing between each pair of slot baffles 12 is 3mm. The slot baffle 12 is vertically inserted into the tank body 1, and a number of flow holes 13 are evenly distributed on the slot baffle 12. The diameter of the flow hole 13 is 8 mm, and the flow hole 13 is used for the flow exchange of the electrolyte. The anode terminal 5 is fixedly installed at the edge position of the top of the tank body 1 on the same side of the anode slot 3, and the cathode terminal 6 is fixedly installed at the edge position of the top of the tank body 1 on the same side of the cathode slot 4. The stirring motor 7 is installed in the center position above the top of the tank body 1. A stirring paddle 11 is connected below the stirring motor 7, and the stirring paddle 11 is arranged inside the tank body 1. A water replenishment hole 17 is arranged on the left side of the stirring motor 7, and a reference electrode mounting hole 18 is arranged on the right side of the stirring motor 7. The reference electrode mounting hole 18 is arranged between the stirring motor 7 and the reference electrode terminal 10. A liquid level monitor 8 is installed at a corner of the top of the tank body 1.

[0039] A test method for a lead-based alloy electrochemical corrosion resistance test device, the specific test steps are as follows:

[0040] 1) Prepare the electrode to be tested 16, the reference electrode 15 and the auxiliary electrode 14;

[0041] Preparation method of the electrode 16 to be tested: melt the lead-based alloy to be tested, cast it into a 10 mm thick lead block, and prepare the lead block into a lead plate with a thickness of 2.5 mm and a surface roughness Ra < 3 μm through multi-stage rolling, and then cut the lead plate into a 60*120 mm electrode piece, and leave a 6 mm wide and 20 mm long electrode ear 29 on the upper part of the electrode piece;

[0042] Preparation method of comparison electrode 15: select a lead alloy that has been tested to meet the alloy standard for battery use and has been actually used to meet the corrosion resistance design requirements within the normal service life cycle of the battery, and use the same preparation method as the electrode to be tested 16;

[0043] Preparation method of auxiliary electrode 14: Select electrolytic lead with a lead content of 99.994%, and use the same preparation method as the electrode 16 to be tested to prepare the auxiliary electrode 14, so that the circuit in the test method can form a complete closed circuit.

[0044] A cadmium electrode is selected as the reference electrode 9, and the reference electrode 9 is immersed in a 1.35±0.01 g / ml sulfuric acid aqueous solution prepared from analytical pure sulfuric acid and distilled water for at least 24 hours; the reference electrode 9 is a standard electrode with a stable potential, and is used to measure the positive electrode potential;

[0045] Prepare the test equipment;

[0046] Prepare a charging test device 23 with a constant voltage and current limiting function as an auxiliary test device, the charging test device 23 includes a positive electrode output line 25, a positive electrode voltage collection line 27, a negative electrode output line 26 and a negative electrode voltage collection line 28;

[0047] With sulfuric acid aqueous solution as the electrolyte, add electrolyte into the tank body 1 through the top of the tank body 1 or the water replenishment hole 17 to the liquid level of 120 mm;

[0048] Weigh the weights of the electrode to be tested 16 and the reference electrode 15 as m1 and m2 respectively;

[0049] 2) Insert the electrode to be tested 16 and the comparison electrode 15 symmetrically into the anode card slot 3, insert the reference electrode 9 into the reference electrode mounting hole 18, and insert the auxiliary electrode 14 into the cathode card slot 4; connect the auxiliary electrode 14 to the cathode terminal 6, and connect the electrode to be tested 16 and the comparison electrode 15 to the anode terminal 5 respectively; add electrolyte to the tank body 1 to the liquid level of 125 mm through the water replenishment hole 17; connect the positive output line 25 and the positive voltage collection line 27 of the charging test equipment 23 to the anode terminal 5, connect the negative output line 26 of the charging test equipment 23 to the cathode terminal 6, connect the negative voltage collection line 28 of the charging test equipment 23 to the reference electrode terminal 10, and connect the water delivery hose 31 controlled by the solenoid valve 19 to the water replenishment hole 17; the connecting components used by the reference electrode 9, the auxiliary electrode 14, the electrode to be tested 16 and the comparison electrode 15 are all their own pole ears 29;

[0050] 3) The test device 32 needs to be placed in a constant temperature water bath at 25±2°C, the stirring motor 7 is started, the stirring speed is set to 5 rpm, and the electrolyte is stirred;

[0051] The control center 21 sends the test program to the charging test device 23 through the charging test device data line 24. The operation data of the charging test device 23 can be fed back to the control center 21 through the charging test device data line 24 and recorded and saved; the liquid level monitor 8 transmits the information to the control center 21 through the liquid level monitor data line 22 by detecting the liquid level. The control center 21 controls the switch of the solenoid valve 19 through the solenoid valve data line 20 based on the fed-back data, thereby controlling the addition or stop of the electrolyte, pure water or distilled water in the test device 32;

[0052] The constant voltage of the charging test equipment 23 is set to 2.6V, and the test is continuously performed for 72 hours at this voltage; the mixture is stirred continuously during the test, and the electrolyte level in the tank 1 is monitored by the liquid level monitor 8. After the liquid level is lowered, pure water or distilled water with a conductivity of less than 1μS / cm in the water storage tank 30 is slowly injected from the water replenishment hole 17 to ensure that the electrolyte level is 125±1mm during the entire test. Since a large amount of oxygen, hydrogen and acidic water vapor are released during the test, the entire test is performed in a fume hood;

[0053] 4) After the test is completed, the electrode to be tested 16 and the reference electrode 15 are taken out from the anode card slot 3, and are immersed in 60°C sugar-alkali water for 15 minutes to remove oxides such as lead dioxide, lead oxide, and lead sulfate produced by surface electrochemical corrosion, and then rinsed with tap water until the surface is bright, and then vacuum dried at 110°C for 30 minutes; wherein, the mass ratio of glucose, caustic soda, and water in the 60°C sugar-alkali water is 1:5:50;

[0054] 5) Use scissors to cut off the tabs 29 of the electrode to be tested 16 and the reference electrode 15, respectively, and weigh the tabs 29 to be m3 and m4, and weigh the remaining electrodes to be m5 and m6;

[0055] Calculate weight loss:

[0056] W1=m5-m3 / m1-m3*100;

[0057] W2=m6-m4 / m2-m4*100;

[0058] △W=W2-W1 / W2*100;

[0059] W1 is the weight loss percentage of the electrode 16 to be tested;

[0060] W2 is the weight loss percentage of the comparative electrode 15;

[0061] △W is the relative corrosion resistance of the electrode to be tested 16. When its value is positive, it means that the corrosion resistance of the electrode to be tested 16 is higher than that of the comparison electrode 15. The higher the ratio, the stronger the corrosion resistance. When its value is negative, it means that the corrosion resistance of the electrode to be tested 16 is lower than that of the comparison electrode 15. The lower the ratio, the worse the corrosion resistance.

[0062] Five samples of the alloy to be tested were prepared according to the preparation method of the present invention, and compared with the same comparative alloy. At the same time, the alloy to be tested was prepared into a grid according to a conventional method, and the corrosion resistance was tested by a constant current method.

[0063] The test results are compared as follows:

[0064]

[0065] Conventional test method (%) represents the weight loss percentage tested according to the conventional method.

[0066] Because the same alloy is tested in parallel, samples 1-5 are made of the same material, and from the test results, by comparing the deviation values ​​between the five samples tested by the same method, it can be seen that the test results using the test device and test method provided by the present invention have small deviation and high stability.

Claims

1. A method for testing a lead-based alloy electrochemical corrosion resistance testing device, the lead-based alloy electrochemical corrosion resistance testing device comprising a tank body (1), It is characterized in that The lead-based alloy electrochemical corrosion resistance test device further comprises a handle (2), an anode slot (3) for placing a comparison electrode (15) and an electrode to be tested (16), a cathode slot (4) for placing an auxiliary electrode (14), an anode terminal (5), a cathode terminal (6), a stirring motor (7), a liquid level monitor (8), a reference electrode mounting hole (18), a reference electrode terminal (10), a stirring paddle (11), a slot baffle (12), a flow hole (13), and a water replenishment hole (17). The handle (2) is mounted on the outer side walls at the front and rear sides of the tank body (1). The anode slot (3) and the cathode slot (4) are relatively parallelly distributed at the front and rear ends of the tank body (1). The anode slot (3) and the cathode slot (4) are each composed of a pair of slot baffles (12). The spacing between each pair of the slot baffles (12) is the same. The slot baffles (12) are spaced apart from each other. ) is vertically inserted into the tank body (1), the slot baffle (12) is evenly distributed with a plurality of flow holes (13), the anode terminal (5) is fixedly mounted on the edge of the top of the tank body (1) on the same side as the anode slot (3), the cathode terminal (6) is fixedly mounted on the edge of the top of the tank body (1) on the same side as the cathode slot (4), the stirring motor (7) is mounted in the middle of the top of the tank body (1), the stirring motor (7) is connected to a stirring paddle (11) below, the stirring paddle (11) is arranged inside the tank body (1), the stirring motor (7) is provided with a water supply hole (17) on the left side, the stirring motor (7) is provided with a reference electrode mounting hole (18) on the right side, the reference electrode mounting hole (18) is arranged between the stirring motor (7) and the reference electrode terminal (10), and a liquid level monitor (8) is installed at a corner of the top of the tank body (1); The specific test steps of the test method are as follows: 1) preparing the electrode to be tested (16), the reference electrode (15) and the auxiliary electrode (14); soaking the reference electrode (9) in a sulfuric acid aqueous solution for at least 24 hours; and preparing a test device; A charging test device (23) with a constant voltage and current limiting function is prepared as an auxiliary test device, wherein the charging test device (23) comprises a positive electrode output line (25), a positive electrode voltage collection line (27), a negative electrode output line (26) and a negative electrode voltage collection line (28); a sulfuric acid aqueous solution is used as an electrolyte, and the electrolyte is added to the tank body (1) to a liquid level of 120 mm; the weights of the electrode to be tested (16) and the comparison electrode (15) are weighed to be m1 and m2 respectively, wherein: Preparation method of the electrode (16) to be tested: melt the lead-based alloy to be tested, cast it into a 10 mm thick lead block, and prepare the lead block into a lead plate with a thickness of 2.5 mm and a surface roughness Ra < 3 μm through multi-stage rolling, and then cut the lead plate into a 60*120 mm electrode piece, and leave a 6 mm wide and 20 mm long electrode ear (29) on the upper part of the electrode piece; Preparation method of comparison electrode (15): select a lead alloy that has been tested to meet the alloy standard for battery use and has been used in practice to meet the corrosion resistance design requirements within the normal service life cycle of the battery, and use the same preparation method as the electrode to be tested (16); Preparation method of the auxiliary electrode (14): electrolytic lead with a lead content of 99.994% is selected, and the auxiliary electrode (14) is prepared by the same preparation method as the electrode to be tested (16); 2) inserting the electrode to be tested (16) and the comparison electrode (15) symmetrically into the anode slot (3), inserting the reference electrode (9) into the reference electrode mounting hole (18), and inserting the auxiliary electrode (14) into the cathode slot (4); connecting the auxiliary electrode (14) to the cathode terminal (6), connecting the electrode to be tested (16) and the comparison electrode (15) to the anode terminal (5), respectively, adding electrolyte to the tank body (1) through the water replenishment hole (17) to a liquid level of 125 mm, connecting the positive output line (25) and the positive voltage collection line (27) of the charging test device (23) to the anode terminal (5), connecting the negative output line (26) of the charging test device (23) to the cathode terminal (6), connecting the negative voltage collection line (28) of the charging test device (23) to the reference electrode terminal (10), and connecting the water supply hose (31) to the water replenishment hole (17); 3) starting the stirring motor (7) and setting the stirring speed to 5 rpm to stir the electrolyte; setting the constant voltage of the charging test device (23) to 2.6V, and conducting the test continuously for 72 hours at this constant voltage; stirring is continued during the test, and the electrolyte level in the tank (1) is monitored by the liquid level monitor (8). After the liquid level is lowered, pure water or distilled water is slowly injected from the water replenishment hole (17) to ensure that the electrolyte level is 125±1 mm during the entire test; 4) After the test is completed, the electrode to be tested (16) and the reference electrode (15) are taken out from the anode slot (3), and immersed in 60°C sugar-alkali water for 15 minutes to remove the oxides produced by surface electrochemical corrosion, and then rinsed with tap water until the surface is bright, and then vacuum dried at 110°C for 30 minutes; 5) Use scissors to cut off the tabs (29) of the electrode to be tested (16) and the reference electrode (15), respectively, and weigh the tabs (29) to be m3 and m4, respectively, and weigh the remaining electrodes to be m5 and m6, respectively; Calculate weight loss: W1=(m5-m3) / (m1-m3)*100; W2=(m6-m4) / (m2-m4)*100; △W=(W2-W1) / W2*100; W1 is the weight loss percentage of the electrode (16) to be tested; W2 is the weight loss percentage of the comparative electrode (15); △W is the relative corrosion resistance of the electrode to be tested (16). When the value is positive, it means that the corrosion resistance of the electrode to be tested (16) is higher than that of the comparison electrode (15). The higher the ratio, the stronger the corrosion resistance. When the value is negative, it means that the corrosion resistance of the electrode to be tested (16) is lower than that of the comparison electrode (15). The lower the ratio, the worse the corrosion resistance.

2. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that The tank body (1) is the main body of the testing device and is made of a 5 mm thick transparent PC material.

3. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that The distance between each pair of the slot baffles (12) is 3 mm.

4. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that The diameter of the flow hole (13) is 8 mm.

5. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that In step 3), the test method is carried out in a fume hood, and the test device (32) needs to be placed in a constant temperature water bath at 25±2°C.

6. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that In step 1), the aqueous sulfuric acid solution is prepared from analytical pure sulfuric acid and distilled water, and the aqueous sulfuric acid solution is 1.35±0.01 g / ml; the reference electrode (9) is a cadmium electrode.

7. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that In step 2), pure water or distilled water with a conductivity of less than 1 μS / cm is introduced into the water delivery hose (31); the connecting components used by the reference electrode (9), the auxiliary electrode (14), the electrode to be tested (16) and the comparison electrode (15) are all their own electrode ears (29).

8. The testing method of the lead-based alloy electrochemical corrosion resistance testing device according to claim 1, It is characterized in that In step 4), the mass ratio of glucose, caustic soda and water in the sugar-alkali water is 1:5:50.

Citation Information

Patent Citations

  • Electrochemical corrosion resistance testing device for lead-based alloy

    CN212872149U